SME Stock Markets in Tropical Economies: Evolving Efficiency and Dual Long Memory. Issue 1 (28th May 2019) - Nguyen, Trang; Chaiechi, Taha; Eagle, Lynne; Low, David
Abstract : This paper examines the evolving efficiency and the joint effects of thin trading, structural breaks and inflation on dual long memory in Small and Medium Enterprise stock markets in Hong Kong, Singapore, Thailand and Malaysia. The state‐space GARCH‐M, ARFIMA‐FIGARCH, ARFIMA‐FIAPARCH and ARFIMA‐HYGARCH models are adopted. The results determine that the Hong Kong and Singapore markets exhibit potential tendencies towards efficiency, implying the efficacy of several institutional reforms. The three aforementioned factors jointly have reducing effects on the magnitude and/or statistical significance of long‐memory estimates. The Thailand and Malaysia markets show a smaller degree of volatility persistence, indicating a good hedge for portfolio risk management.